2020
DOI: 10.3390/agronomy10040521
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Nitrogen Practice in Winter Wheat-Summer Maize Rotation Affecting the Fates of 15N-Labeled Fertilizer

Abstract: Lower nitrogen recovery efficiency (NRE) and negative environmental impacts caused by excessive nitrogen (N) fertilization threaten the sustainability of agriculture. Efficient and appropriate fertilization practices are extremely important to achieve higher crop yield with minimum N loss. A field microplot experiment was conducted in a wheat-maize rotation system in Shaanxi province, at North China Plain, using the 15N isotope tracer technique to qualify the different annual N managements in terms of crop yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
2
7
0
1
Order By: Relevance
“…This suggested that a major portion of the nitrogen that accumulates in the wheat grains at harvest originates from the degradation of proteins in senescing and falling vegetative segments ( Bouchet et al, 2016 ). The application of fertilizer in appropriate proportions can results in greater nitrogen accumulation in the vegetative parts until anthesis ( Liang et al, 2020 ). Similarly, we report that the N3 treatment significantly increased the nitrogen accumulation of wheat plants during anthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that a major portion of the nitrogen that accumulates in the wheat grains at harvest originates from the degradation of proteins in senescing and falling vegetative segments ( Bouchet et al, 2016 ). The application of fertilizer in appropriate proportions can results in greater nitrogen accumulation in the vegetative parts until anthesis ( Liang et al, 2020 ). Similarly, we report that the N3 treatment significantly increased the nitrogen accumulation of wheat plants during anthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the past four decades, global maize production has greatly increased (FAO, 2018) mainly due to application of nitrogen (N) fertilizers. Worldwide, N fertilizer has widely been excessively applied to achieve higher grain yields (Cui et al, 2009;Meng et al, 2016;Liang et al, 2020). For example, the average dose of N fertilizer applied by the farmers was field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from the perspective of actual production, our study showed that, with the increase in groundwater depth, both yield and its growths decreased from no significant difference under low to middle N application (150-240 kg/ha) to significantly decreased under high N application (300 kg/ha), indicating that the deeper groundwater depth would obtain the great potential of reduction N application. Particularly in recent years, a large amount of fertilizer has been applied, and groundwater was overexploited on the NCP to get high yields, which have resulted in a much lower groundwater table (>1.5 m) [39,56], and a thicker vadose zone year by year, leading to a large amount of seasonal nitrogen residue in the soil and the next crop is planted with high background nitrogen content [39,[57][58][59]. Therefore, it is feasible to reduce the N application by 20% on the NCP, based on our study, without the influence of crops yield.…”
Section: Winter Wheat Yield and Its Componentsmentioning
confidence: 99%